Dictatorship, Necropolitics, and the Collapse of Resistance in La Vie et demie by Sony Labou Tansi - Onomejoh , Princewill Onomejoh; Eriel, Ehigie, Dare (Journal of Science and Knowledge Horizons, 2025)
This paper explores the strategic deployment of violence by the Guide Providentiel in La Vie et demie by Sony Labou Tansi, revealing how authoritarian regimes weaponize cruelty to dominate, silence dissent, and psychologically dismantle resistance. Drawing on Achille Mbembe’s concept of “necropolitics,” the analysis shows how the Guide transforms his state into a theatre of horror, where ritualized executions, mutilations, and grotesque spectacles become tools for political control. The novel’s depiction of torture, including the use of eating utensils to dismember bodies and force victims’ children to consume human flesh, reflects a deliberate aestheticization of violence intended to break not only bodies but spirits. The Guide’s totalitarian cruelty is also intergenerational: he eliminates the children of revolutionaries to prevent future resistance. However, the narrative reveals the limits of violence; figures like Chaïdana resist intellectually and symbolically, undermining the Guide’s authority through subversive acts. The study draws on scholarly works by Mbembe, Sepas, Diop, MacLeod, and Mahala to frame Tansi’s portrayal of sovereignty, suffering, and absurdity within postcolonial African contexts. It also considers the ghostly return of Martial and Chaïdana’s revolutionary sabotage to argue that while violence may suppress the body, it cannot eliminate the will to resist. The Guide’s failure to achieve total domination underscores the resilience of oppressed voices and highlights how violence, when pushed to its extremes, becomes self-defeating